Financial Distress: Studi Intellectual Capital dan Karakteristik Direksi pada Perusahaan Ritel di Indonesia - Wawan Cahyo Nugroho (Owner : Riset dan Jurnal Akuntansi, 2025)
This research aims to examine the influence of Intellectual Capital and directors' characteristics on financial distress. This research used 90 samples from 15 retail companies listed on the Indonesia Stock Exchange in 2017-2022. Technical data analysts use multiple linear regression. The research results show that intellectual capital has a significant positive effect on financial distress because the value of intellectual capital is a hidden value that gives companies a competitive advantage. This research shows that companies with high intellectual capital values ??will significantly improve their financial conditions and will not experience financial problems. Gender diversity of the board of directors has a significant negative effect on financial distress. This is because in Indonesia, there are still few female board directors and female directors need more time to take policies in predicting company bankruptcy. The age of directors does not have a significant effect on financial distress. This is because young directors, who are considered more open to new things and have a more dynamic way of thinking, will not necessarily benefit the Company if they are not balanced with mature calculations, emotional control and a consistent mindset. Directors' education has a significant positive effect on financial distress, this is because educational background will influence the knowledge possessed by having existing business and economic knowledge so that they have better abilities to manage the business and provide direction in predicting the company's financial distress.